Diurnal intraocular pressure variations: an analysis of 690 diurnal curves. Issue 5 (May 1992) - David, R; Zangwill, L; Briscoe, D; Dagan, M; Yagev, R; Yassur, Y
Abstract : Out of a total of 2272 diurnal curves (DC) of intraocular pressure (IOP) obtained from 1178 patients 690 first curves of the right eye of all patients were analysed. For each DC there were 4-6 IOP readings taken between 8 am and 6.30 pm of the same day. The patients' diagnosis, age, sex, type of IOP lowering medication, diabetes, and the calendar month of the year were recorded. In 40% of cases the highest IOP was found at the earliest morning measurement with some 65% of peaks occurring before noon. The lowest IOP measurement showed no specific predilection for any particular time of the day. These findings were true for all diagnosis groups. The mean range of IOP fluctuation during the DC was 5.0 mm Hg in normals, 5.8 mm Hg in patients with open angle glaucoma (OAG), and 6.8 mm Hg in patients with ocular hypertension (OHT). Patients treated with timolol had a lower mean IOP fluctuation range than those on other types of IOP lowering treatment. No association was found between all other parameters examined and the diurnal IOP distribution.